Dynamical analysis of erythrocytes under the assumption of cross-spectral coherence between blood cell counts and the Dst index - E. A. Fernández; P. Willshaw; J. Ure; F. Carusela; L. Romanelli; C. A. Perazzo; S. Dasso (Geofísica internacional, 2004)
The possible influence of solar activity on human health through magneto-biological mechanisms is a prominent and controversial matter. Several physical mechanisms that occur in the Sun can affect the interplanetary environment of the Earth, and produce perturbations in the geomagnetic field. The Dst index, which measures the average disturbance magnetic field at the Earth’s equator, is a good indicator of these global magnetic fluctuations. Erythrocytes, platelets and leukocytes play a key role in living systems because they are responsible for the transport of oxygen, coagulation and the immune response respectively. In the healthy subject, blood cell counts fluctuate and it is customary to talk of normal ranges or maximal limits. However, it has recently been reported that these fluctuations are scale-invariant. Daily fluctuations in the number of a given type of blood cell are expected to reflect the intrinsic dynamics of the hematologic system and its response to various intrinsic and extrinsic perturbations. We analyze blood cell counts from two sheep over 1024 consecutive days, and the Dst index. We found a low correlation between these temporal series, but we do find a significant correlation in frequency space. A significant peak around seven days is found in both series.